2023
DOI: 10.1029/2023ea003043
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Water Seafloor Geodesy With Wave Glider‐Based GNSS‐Acoustic Surveying of a Single Transponder

Surui Xie,
Mark Zumberge,
Glenn Sasagawa
et al.

Abstract: Due to the blockage of seawater, seafloor displacement cannot be directly measured by space geodesy. The combination of Global Navigation Satellite Systems‐acoustic ranging (GNSS‐A) has been used to overcome the electromagnetic barrier, so that a GNSS‐determined sea surface vessel's coordinates can be transformed to seafloor benchmarks in a global reference frame. Due to the high cost and science priorities, previous GNSS‐A studies mainly targeted relatively deep water and a minimum of three transponders were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For the field of underwater detection using wave gliders, Surui Xie [10] designed measurement trajectories and found that the GNSS-a based on wave gliders can provide centimeter-level horizontal positioning accuracy for a single transmitter in shallow water, even if the sound speed model differs from the actual value by a few meters per second, making low-cost GNSS-A surveys in shallow water areas a promising reality. Zhilin Lyu [11] proposed a real-time ship detection system based on the YOLOv5s lite CBAM model, equipped with a visual detection and recognition system using a wave glider.…”
Section: Introductionmentioning
confidence: 99%
“…For the field of underwater detection using wave gliders, Surui Xie [10] designed measurement trajectories and found that the GNSS-a based on wave gliders can provide centimeter-level horizontal positioning accuracy for a single transmitter in shallow water, even if the sound speed model differs from the actual value by a few meters per second, making low-cost GNSS-A surveys in shallow water areas a promising reality. Zhilin Lyu [11] proposed a real-time ship detection system based on the YOLOv5s lite CBAM model, equipped with a visual detection and recognition system using a wave glider.…”
Section: Introductionmentioning
confidence: 99%